COPING STRESS PADA MAHASISWA YANG BEKERJA - Lubis, Rahmi; Irma, Nova Hapizsyah; Wulandari, Rafika; Siregar, Khairunnisa; Tanjung, Nur Annisa; Wati, Tia Agustina; N, Miranda Puspita; Syahfitri, Diah (Psychology Department Faculty of Psychology Universitas Medan Area, 2015)
This study aimed to describe the coping strategies by working students. Respondents are 5 working students. Data collected by interview and observation methods. The results showed that of the five respondents note that the source of stress is difficult to manage time on doing their tasks, workloads and schedules collide, and not easy to get permission to attend the classes. At respondents 2 and 5, less family support while respondents 4, co-workers who do not support. Respondents 5, there are transportation constraints. The coping strategies that do fifth respondent is to be open to the closest associates and families, assertive to the boss, and try to look at the issues more positively. In the second respondent also doing hobbies with friends and did not procrastinate. On 3 respondents anticipated by ditching college and make it a priority. In the fourth respondent, trying to avoid problems with sleep, surrender to God, and to receive advice from others. While the respondent 5, grateful and try to control his emotions. Can be seen on the respondents 1 and 3, their own colleagues and family support them so that they can solve the problems they face.Keyword: Working, Coping, Stress, College Student.